Goods Management System Using Always Better Control (ABC) Method - Prasetyo, Adi Tri; Hasanah, Herliyani; Oktaviani, Intan (Politeknik Negeri Lhokseumawe, 2025)
This study aims to design and develop a web-based inventory management system utilizing the Always Better Control (ABC) method to assist Toko Didik in managing stock more efficiently. Until now, the inventory process in the store has been carried out manually using conventional record-keeping, which is prone to data entry errors, delays in stock monitoring, and the absence of a classification system to prioritize items based on their sales contribution.To address this problem, the system was designed using the Waterfall development methodology, involving stages of requirements analysis, system design, implementation, and testing. Data were collected through observation, interviews, and documentation conducted at the store site. The system was built using the Laravel framework and MySQL database, and includes key features such as item recording, automatic item classification using the ABC method, real-time stock monitoring, purchase recommendations, sales transactions, and sales reporting. The results of black-box testing indicate that all system functions operate as expected without errors. The ABC classification method successfully groups items into three categories based on their contribution to total sales, allowing the store owner to prioritize procurement effectively. With this system, inventory management becomes more organized, accurate, and supports data-driven decision-making. This study serve as an alternative solution for small or medium-sized stores in addressing inventory management challenges through the use of information systems.